(untitled) (Journal of the College of Education for Women, 2019)
The personality of an individual comes from the social adjustment which isrepresented by the individual interaction with the others. If the individual has acceptableadjustment, he/she has good social skills such as the flexibility in interaction with others andaccepting the living with them.Sometimes, the individual show pretended personality in his/her interaction withothers and we should accept the appearance of this characteristic in society. An individuallives in this society among different types of human personalities with his own personalitywhich represents emotional, social, rational and physical characteristics.These characteristics have their importance to be studied within college studentsbecause of the students’ vital role in the development of the society. The students facedifferent challenges to satisfy their hopes and dreams which may have negative effect on thehome and society.The problem of this study could be clarified by answering the following question: Dothe University of Baghdad students have pretended personality?The present study aims at measuring the pretended personality of the University ofBaghdad students male and female at first and fourth stages for the academic year 2012-2013.The sample of the study is (500) students selected randomly and the study tool isconstructed by the researcher.